2016
DOI: 10.1016/j.jclepro.2016.01.085
|View full text |Cite
|
Sign up to set email alerts
|

Corporate characteristics and environmental management accounting (EMA) implementation: evidence from Malaysian public listed companies (PLCs)

Abstract: Adopting the contingency theory framework, this study investigated the extent to which Malaysian public listed companies (PLCs) implement environmental management accounting (EMA) and whether the implementation varies across corporate characteristics. Five corporate characteristics, namely, environmental sensitivity of industry, company size, ownership status, Environmental Management System (EMS) adoption and the proportion of non-executive directors (NEDs), were examined. The results, derived from postal que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 66 publications
6
62
0
9
Order By: Relevance
“…Jalaludin et al (2010) provided that EMA implementation is moderate, but their results produce positive correlations between EMA (monetary and physical) and environmental performance. A more recent study by Mokhtar, Jusoh, and Zulkifli (2016) found that EMA implementation is moderate, but which has shown an increase from previous studies. This could be an indicator that EMA is slowly but surely gaining more interest.…”
Section: Hypothesis Developmentmentioning
confidence: 80%
See 2 more Smart Citations
“…Jalaludin et al (2010) provided that EMA implementation is moderate, but their results produce positive correlations between EMA (monetary and physical) and environmental performance. A more recent study by Mokhtar, Jusoh, and Zulkifli (2016) found that EMA implementation is moderate, but which has shown an increase from previous studies. This could be an indicator that EMA is slowly but surely gaining more interest.…”
Section: Hypothesis Developmentmentioning
confidence: 80%
“…According to Schaltegger, Hahn, and Burritt (2000), physical EMA is used primarily for the setting of goals and targets in order to monitor and control the environment. Thus, EMA can be used to determine day to day operations and strategies providing for better environmental information as the absence of proper measurement of environmental information hinders companies from generating relevant information for decision-making (Schaltegger et al, 2000;Burritt et al, 2003;Mokhtar et al, 2016).…”
Section: Environmental Management Accountingmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of environmental activities include pollution control investment data (Peng & Yang, 2014), deployment of a carbon-reduction strategy (Cadez & Czerny, 2016;Lee, 2012;Liu, 2012;Liu & Liu, 2016), eco-control usage (Henri & Journeault, 2010), the ratio of toxic waste recycled to total toxic waste generated (Al-Tuwaijri, Christensen, & Hughes, 2004), adoption of global environmental standard (Dowell, Hart, & Yeung, 2000), environmental proactivity (Primc & Čater, 2015), environmental management accounting implementation (Mokhtar, Jusoh, & Zulkifli, 2016), environmental sustainability policies (Naranjo-Gil, 2016), etc. Examples of philanthropic activities include donations (Lin, Yang, & Liou, 2009), growth in charitable contributions (Lev, Petrovits, & Radhakrishnan, 2010) and public health policies (Naranjo-Gil, Sánchez-Expósito, & Gómez-Ruiz, 2016).…”
Section: One-dimensional Measuresmentioning
confidence: 99%
“…In other words, EMA incorporates two types of environmental information, namely, physical and monetary (Mokhtar et al, 2016). Physical environmental information refers to the flow of energy, water, materials and wastes, for instance the total volume of wastes and energy consumed and the total amount of fresh water consumed.…”
Section: The Concept Of Environmental Management Accountingmentioning
confidence: 99%